O kosmologicznych tradycjach badawczych - Sierotowicz, Tadeusz (Filozofia Nauki, 1996)
In the paper the conception of Cosmological Research Tradition, founded on the methodology of scientific research tradition introduced by L. Laudan, is proposed. A brief remark of the status of various problems in the domain of philosophy of science is also given.